Perancangan Dan Pembangunan Sistem Informasi Jual Beli Barang Bekas Berbasis Website Studi Kasus UD Candi Rosok Ds. Bagi Kec. Madiun Kab Madiun - Alcho Anggara (CV. ITTC INDONESIA, 2025)
This research aims to design and implement an information system for buying and selling used goods at UD Candi Rosok, Bagi Village, Madiun District, Madiun Regency. The system was designed using a structured approach by utilizing flowcharts, entity relationship diagrams, and data flow diagrams, and was built using the PHP programming language, CodeIgniter 4 framework, and MySQL database. The design process includes identifying user needs, creating a database design, and developing a user interface. The system implementation successfully integrates features such as goods registration, buying and selling transactions, and transaction reports which make it easier to manage data on used goods and transactions between sellers and buyers. The test results with the System Usability Scale (SUS) score show a score of 75.25, which is included in the